Pinkas, kahal, and the mediene : the records of Dutch Ashkenazi communities in the eighteenth century as historical sources - Litt, Stefan, 1969- (Leiden ; Boston : Brill, 2008)
Scholars of the rich history of the Jews in the Dutch Republic have tended to concentrate on the remarkable story of Amsterdam. This study examines the records of four provincial Ashkenazi communities in eighteenth-century Netherlands including The Hague, Middelburg, Leeuwarden, and Oisterwijk.
Governing a Jewish community -- Keeping a pinkas -- Officials of the Jewish community -- Members, origins, and patterns of migration -- Revenue and finance -- Hevras and charities -- Intercommunal frameworks -- Conclusions.
Includes bibliographical references (pages 193-196) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Ashkenazim -- Netherlands -- Hague -- History -- 18th century -- Sources; Ashkenazim -- Netherlands -- Leeuwarden -- History -- 18th century -- Sources; Ashkenazim -- Netherlands -- Middelburg -- History -- 18th century -- Sources; Ashkenazim -- Netherlands -- Oisterwijk -- History -- 18th century -- Sources; Ashkenazim -- Netherlands -- Politics and government -- 18th century -- Sources; Hague (Netherlands) -- Ethnic relations -- History -- Sources; Leeuwarden (Netherlands) -- Ethnic relations -- History -- Sources; Middelburg (Netherlands) -- Ethnic relations -- History -- Sources; Oisterwijk (Netherlands) -- Ethnic relations -- History -- Sources; Ashkénazes -- Pays-Bas -- La Haye -- Histoire -- 18e siècle -- Sources; Ashkénazes -- Pays-Bas -- Leeuwarden -- Histoire -- 18e siècle -- Sources; HISTORY -- General; Ashkenazim; Ethnic relations; Netherlands; Netherlands -- Hague; Netherlands -- Leeuwarden; Netherlands -- Middelburg; Netherlands -- Oisterwijk; Quelle; Niederlande; Jüdische Gemeinde; Aschkenasim; 1700-1799; History; Sources